2022
DOI: 10.46604/ijeti.2022.8599
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Compressive Sensing for Joint Compression and Encryption of Sensor Data

Abstract: The security and energy efficiency of resource-constrained distributed sensors are the major concerns in the Internet of Things (IoT) network. A novel lightweight compressive sensing (CS) method is proposed in this study for simultaneous compression and encryption of sensor data in IoT scenarios. The proposed method reduces the storage space and transmission cost and increases the IoT security, with joint compression and encryption of data by image sensors. In this proposed method, the cryptographic advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Sensor nodes range from straightforward devices such as temperature monitors to complex systems like surveillance cameras, and they determine the nature and format of the data collected. These nodes are increasingly being equipped with edge computing capabilities, which allow for a degree of local data preprocessing [14]. Even less resource-intensive sensors can engage in basic edge computing tasks by employing streamlined algorithms and optimized firmware tailored to their processing abilities.…”
Section: Sensor Nodesmentioning
confidence: 99%
“…Sensor nodes range from straightforward devices such as temperature monitors to complex systems like surveillance cameras, and they determine the nature and format of the data collected. These nodes are increasingly being equipped with edge computing capabilities, which allow for a degree of local data preprocessing [14]. Even less resource-intensive sensors can engage in basic edge computing tasks by employing streamlined algorithms and optimized firmware tailored to their processing abilities.…”
Section: Sensor Nodesmentioning
confidence: 99%
“…Sudarsono et al [20] suggested a method that uses CP-ABE and Hashed MAC to securely transfer environmental data from sensor nodes to a gateway while maintaining integrity. To safely encrypt the sensor data, Chatamoni et al [21] adopted a portable compressive sensing technology that uses structurally random matrices and blocks compressive sensing.…”
Section: Related Workmentioning
confidence: 99%